“Better to Lose your Eyes than your Name”: The Ineffectiveness Trap of Sport Integrity Reporting Mechanisms - Moriconi, M.; Verschuuren, Pim; Clemence Collon (IPSA RC20 Political Finance and Political Corruption Bi-annual Meeting, 2026)
In particular with the advent of online betting, the manipulation of sports competitions became one of the greatest corrupt threats. Governments, law enforcement institutions and sport organisations have created new joint structures to combat this scourge. Among these structures are the National Platforms (NPs) against the manipulation of competitions, created on the recommendation of the Council of Europe Macolin Convention. Those NPs need information from reporting persons to detect, investigate and sanction wrongdoing. Scientific literature about whistleblowing in sport underlines the ethical dilemmas surrounding manipulation situations, and the difficulties and constraints for sport stakeholders to speak up against integrity wrongdoings. Through a documentary analysis and a set of interviews and focus groups with 79 athletes, coaches, referees and representatives of National Platforms, the paper examines to what extent NPs of four countries (France, Portugal, Greece and Cyprus) have managed to attract reports and explores what fosters or constrains whistleblowing actions from sport actors. The findings underline both the national reporting policies lack of maturity and their general failure in attracting substantial reports, despite policy variations between the four countries. Several key cross-country factors contribute to the reluctance to report: the precarious power position of on-field sport actors, the poor quality of sport governance and the distrust towards authorities. Implemented policies and their authorities are perceived as inadequate and disconnected from the stakeholders' realities and needs. Policy dissonance fosters even more cynicism and further deteriorates reporting attitudes and intentions. Our findings contribute to a fast-developing research field on national and international sport integrity by proposing a first assessment of the NPs. They demonstrate the need for more structural and coherent national sport integrity policies and invite researchers to use holistic approaches to better understand their implementation processes and their effects.